African Approaches to Intellectual Property: Intellectual Property, Development and the Contested Meanings of Decolonisation - Ntokozo Dladla (International Journal of Critical Diversity Studies)
The term “decolonisation” has been revived more recently in intellectual property (IP) jurisprudence. This article attempts to trace the evolution of its usage in the work of two prominent IP scholars, Ruth L. Okediji and Caroline B. Ncube. I argue that in the work of Okediji, the term is used to renew the radical debates of the 1970s on the right to development in order to undo international law and IP’s imperialist correlates. In the work of Ncube, on the other hand, the term is used to disarticulate the “literal” meaning of decolonisation (1955–1975) from the historical exigencies which necessitated the emergence of African approaches to international law. Whereas “decolonisation” in the work of Okediji is applied to expand the disciplinary framework of African approaches to international law within the field of IP, Ncube idealises the term in order to redeem the development enterprise and obfuscate its racialising discourse of Africa. Ultimately, this article aims to provide a contribution to the historiography of African international legal scholarship by examining the contested meanings of “decolonisation” within IP’s disciplinary present. “Each new concept bristles with its own complications, and it is not to be imagined that the mere resort to certain terminology is the answer to everything” ( Rodney, 1972 , p. 13).